A bacterial protease inhibitor protects antigens delivered in oral vaccines from digestion while triggering specific mucosal immune responses - Ibañez, Andres Esteban (2015)
We report here that a bacterial protease inhibitor from Brucella spp. called U-Omp19 behaves as an ideal constituent for a vaccine formulation against infectious diseases. When co-administered orally with an antigen (Ag), U-Omp19: i) can bypass the harsh environment of the gastrointestinal tract by inhibiting stomach and intestine proteases and consequently increases the half-life of the co-administered Ag at immune inductive sites: Peyer's patches and mesenteric lymph nodes while ii) it induces the recruitment and activation of antigen presenting cells (APCs) and increases the amount of intracellular Ag inside APCs. Therefore, mucosal as well as systemic Ag-specific immune responses, antibodies, Th1, Th17 and CD8(+) T cells are enhanced when U-Omp19 is co-administered with the Ag orally. Finally, this bacterial protease inhibitor in an oral vaccine formulation confers mucosal protection and reduces parasite loads after oral challenge with virulent Toxoplasma gondii.